Microstructural Evolution of Nb–V–Mo and V Containing TRIP-assisted Steels during Thermomechanical Processing. Issue 4 (April 2017) - Abbasi, Erfan; Rainforth, William Mark
Abstract : The microstructural evolution and precipitation behaviour of Nb–V–Mo and single V containing transformation induced plasticity assisted steels were investigated during thermomechanical processing. A plane strain compression testing machine was used to simulate the thermomechanical processing. Microstructures were characterised by optical microscopy, scanning-transmission electron microscopy and microanalysis, and X-ray diffraction analysis, and Vickers hardness was obtained from the deformed specimens. The resulting microstructure of both Nb–V–Mo and V steels at room temperature primarily consisted of an acicular/bainitic ferrite, retained austenite and martensite surrounded by allotriomorphic ferrite. The TEM analysis showed that a significant number of Nb(V, Mo)(C, N) precipitates were formed in the microstructure down to the finishing stage in Nb–V–Mo steel (i.e. 830 °C). It was also found that the V(C, N) precipitation primarily occurred in both ferrite and deformed austenite below the finishing stage. The results suggested that Nb–Mo additions considerably increased the temperature stability of microalloy precipitates and controlled the microstructural evolution of austenite. However, the microalloy precipitation did not cause a significant precipitation strengthening in both Nb–V–Mo and V steels at room temperature.